SISTEM KEWARISAN DALAM PERSPEKTIF HUKUM ISLAM DAN PERATURAN PERUNDANG-UNDANGAN DI INDONESIA - Astrid Pane (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2023)
Inheritance law according to Islamic law is one part of family law (al-Ahwalus Syahsiyah). This science is very important to learn so that in the implementation of the division of inheritance there is no mistake and can be carried out as fairly as possible, because by studying the Islamic inheritance law for Muslims, will be able to fulfill the rights relating to inheritance after being abandoned by Muwarris (heir) and submitted to the heirs who have the right to receive it. Thus, one can avoid sin, namely not eating the property of people who are not their rights, because there is no fulfillment of Islamic law regarding inheritance. The inheritance legal system according to the Civil Code does not distinguish between sons and daughters, between husbands and wives, they have the right to inheritance, and the sons share sons and daughters, the part of a wife or husband is the same as the child. When linked to the hereditary system, the Civil Code adheres to a bilateral descent system, where each person connects himself to the descendants of his father and mother, meaning that heirs are entitled to inherit from the father if the father dies and has the right to inherit from the mother if the mother dies.